Program P5 sebagai Implementasi Kurikulum Merdeka: Faktor Penghambat dan Upayanya - Annisa Intan Maharani; Istiharoh Istiharoh; Pramasheila Arinda Putri (Atmosfer: Jurnal Pendidikan, Bahasa, Sastra, Seni, Budaya, dan Sosial Humaniora, 2023)
This study aims to analyze the P5 Program as an implementation of the Merdeka Curriculum in the context of potential inhibiting factors. The literature review method was employed to gather information related to identified inhibiting factors in the implementation of the P5 Program. Searches were conducted in educational literature, academic journals, and publications related to the implementation of the Merdeka Curriculum and the P5 Program. Based on the literature analysis, the identified inhibiting factors include resource readiness, teacher understanding, and preparedness, as well as time and space limitations. To address these factors, proposed efforts encompass increasing educational investment, teacher training, and development, as well as collaboration between schools and the community. The findings of this study provide valuable insights for educational practitioners and decision-makers in identifying and overcoming inhibiting factors in the implementation of the P5 Program, thus enhancing the effectiveness and success of the program in achieving the desired educational goals.